2004
DOI: 10.1073/pnas.0400357101
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a significant urbanization effect on climate in China

Abstract: China has experienced rapid urbanization and dramatic economic growth since its reform process started in late 1978. In this article, we present evidence for a significant urbanization effect on climate based on analysis of impacts of land-use changes on surface temperature in southeast China, where rapid urbanization has occurred. Our estimated warming of mean surface temperature of 0.05°C per decade attributable to urbanization is much larger than previous estimates for other periods and locations. The spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
511
1
11

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 755 publications
(546 citation statements)
references
References 29 publications
23
511
1
11
Order By: Relevance
“…The assumption here is that reanalyses do not know about changes in land use. Initial work in this area was suggestive of a large effect [e.g., Zhou et al (2004) for southern China], but more detailed studies over different parts of China and for different periods showed results were very susceptible to the choices of region and period. Figure 1 shows hemispheric and global averages from the four groups, with results expressed as anomalies from the 1961-90 base period used by HadCRUT4.…”
Section: Comparison With Reanalysesmentioning
confidence: 99%
“…The assumption here is that reanalyses do not know about changes in land use. Initial work in this area was suggestive of a large effect [e.g., Zhou et al (2004) for southern China], but more detailed studies over different parts of China and for different periods showed results were very susceptible to the choices of region and period. Figure 1 shows hemispheric and global averages from the four groups, with results expressed as anomalies from the 1961-90 base period used by HadCRUT4.…”
Section: Comparison With Reanalysesmentioning
confidence: 99%
“…For its unique low-light imaging capacity, the nighttime light imagery can not only be used as the characteristic index in the analysis of urbanization effect, but also meet the needs of detection in human activities [49,50]. In terms of Zhou et al [29] and Hu et al [35], the urbanization process in China primarily started around 1979. Therefore, observed data during the period from 1979 to 2008 in eastern China (15°-54°N, 110°-136°E) is used in the following analysis.…”
Section: Data Sources and Homogeneity Adjustmentmentioning
confidence: 99%
“…The OMR method is based on the fact that the reanalysis data did not assimilate observed surface information. This method does provide some signatures consistent with the distribution of underlying surface properties [22,[29][30][31][32][33][34][35][36]. However, whether or not the OMR fully represents the impact of LUCC is still controversial [37,38].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of urbanization are largely contingent on the size, location, and configuration of development (Weng, 2001;Zhou et al, 2004), with many environmental impacts exacerbated when new growth is expansive and/or fragmented in form (Alberti, 2005). A meta-analysis of urban expansion indicates that localto regional-scale studies are geographically biased, leaving even many large cities unstudied (Seto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%